2013
DOI: 10.1371/journal.pone.0081776
|View full text |Cite
|
Sign up to set email alerts
|

Early Increase and Late Decrease of Purkinje Cell Dendritic Spine Density in Prion-Infected Organotypic Mouse Cerebellar Cultures

Abstract: Prion diseases are infectious neurodegenerative diseases associated with the accumulation of protease-resistant prion protein, neuronal loss, spongiform change and astrogliosis. In the mouse model, the loss of dendritic spines is one of the earliest pathological changes observed in vivo, occurring 4–5 weeks after the first detection of protease-resistant prion protein in the brain. While there are cell culture models of prion infection, most do not recapitulate the neuropathology seen in vivo. Only the recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…PrP Sc is often found in neuropil deposits, which are referred to as ‘synaptic‐like’, as they appear to surround synaptic sites (Clinton et al ., 1993; Belichenko et al ., 2000; Cunningham et al ., 2003; Campeau et al ., 2013). In prion diseases, apart from neuronal loss, earliest and potentially most vital neuropathology changes occur at the level of synapses including synapse loss, morphological changes, and functional abnormality (Mallucci, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…PrP Sc is often found in neuropil deposits, which are referred to as ‘synaptic‐like’, as they appear to surround synaptic sites (Clinton et al ., 1993; Belichenko et al ., 2000; Cunningham et al ., 2003; Campeau et al ., 2013). In prion diseases, apart from neuronal loss, earliest and potentially most vital neuropathology changes occur at the level of synapses including synapse loss, morphological changes, and functional abnormality (Mallucci, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prion-infected cerebellar slice cultures were established as previously described (17,18), using 10-to 12-day-old tga20/ϩ mice (19). Sagittal slices (350 m thick) of cerebellum were prepared and treated with 1.0 g of RML prion-infected or uninfected brain homogenates/ml as free-floating sections for 1 h on ice before washing and plating.…”
Section: Methodsmentioning
confidence: 99%
“…Given the partial efficacy of the bile acids in two cell culture models of prion infection, we examined their effect on the replication of PrP Sc in cerebellar slice culture. The prion organotypic slice culture assay (POSCA) allows prion replication ex vivo under conditions that closely resemble intracerebral infection (17,18). In addition, it has been demonstrated that this assay predicts in vivo efficacy of drug treatment more accurately than cell-based assays (30).…”
Section: Effect Of Bile Acids On the Efficiency Of Prpmentioning
confidence: 99%
See 2 more Smart Citations